(untitled) (Bulletin KNOB, 2001)
In 1767 the physician and scientist Petrus Camper (1722-1789) made an anonymous attack on ’the taste of the Netherlands’ in the journal De Philosooph. Thereby he elaborately directed his arrows at Dutch architecture and particularly at the Amsterdam Town Hall, which had been internationally renowned since the seventeenth century. Not long afterwards the well-known Amsterdam art collector Cornelis Ploos van Amstel (1726-1798) published his defense in a detailed pamphlet. In so far as known this developed into the first architecture polemic fought out in the Dutch press, which is particularly interesting in view of the important position of the two opponents. Petrus Camper is considered one of the major Dutch scientists of the eighteenth century, who was uncommonly interested in architecture. He was an honorary member of the Amsterdam academy of art, published on the subject of aesthetics (‘over het gedaante schoon’ [on the beauty of form]) and was one of the initiators of the contest for a new town hall in Groningen in 1772. In Camper’s opinion Dutch architecture could be blamed for lack of taste and an inclination to imitate, both in his own time and in the seventeenth century. According to him this could be solved by informing art lovers and artists of the modern aesthetics or theory of beauty especially promoted by English and French philosophers. Ploos van Amstel, also a prominent member of the Amsterdam academy of art and besides an advocate of the reappraisal of seventeenth-century Dutch landscape art, was considered one of the major art connoisseurs in Amsterdam. Camper’s frontal attack on the Town Hall, by that time the example of the glory of the Golden Age and thus unassailable in advance, induced Ploos to a defense that is emotional and chauvinist rather than consistent. In many places he refers to Camper’s faulty terminology, but on the other hand does not mention that Camper was very well-informed of the changing ideas in international theory of architecture. Although Camper does not use the correct terminology, he does succeed in questioning Dutch taste, which had degenerated into something alien due to habituation and blind trust in the authority of the classics with their absolute proportions for the use of the colonnades. Although this polemic appeared to invite further discussion, so far it is not known what impact it had on the further development of Dutch architecture.